PROCESSING OF OUTPUT OF OIL-FAT INDUSTRY - Крыжак, Лилия; Фиалковская, Лариса (Modern engineering and innovative technologies, 2022)
In the paper, an analysis of the modern state of methods of purification of sunflower oil from concomitant impurities is carried out. The main tasks of the oil-fat industry as a holistic system of management and production of food raw materials and food p